ETIKA MENCARI ILMU DAN RELEVANSINYA DALAM PENDIDIKAN ISLAM MODERN ANALISIS KITAB WASHOYA, KARYA SYAIKH MUHAMMAD SYAKIR - Muhammad Nabil; Abdul Hamid; Umi Lailia Maghfiroh (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
The objectives of this journal are analyzing the idea of studying the concept of adab studying in the Book of Washoya by Shaikh Muhammad Syakir, and how is this idea used in contemporary Islamic teaching? The journal will offer insights for Islamic educators and thinkers on how the idea of adab studies in the Book of Washoya can be utilized in contemporary Islamic education as a way to safeguard Islamic values and create a quality generation of civilized Muslims. Research is literature research. Documents from previous research articles related to the study of adab studying in the book of Washoya by Shaikh Muhammad Syakir were used as the primary data source for this study. While the data analysis approach uses primary and secondary data analysis techniques. Study Results: 1. The Book of Washoya by Shaikh Muhammad Syakir emphasizes good attitudes and ethics when seeking knowledge. 2. Students can understand and absorb the material they have received by using the concept of adab learning in the book of Washoya, thus making them more enthusiastic and encouraged to continue learning. The principle of adab learning in the learning process needs to be emphasized and strengthened in modern Islamic education if students are to absorb knowledge properly and appropriately.